The impact of portfolio assessment on Iranian EFL students’ essay writing: a process-oriented approach - Behrooz Ghoorchaei,; Mansoor Tavakoli,; Dariush Nejad Ansari, (Penerbit UKM, 2010)
This study investigates the impact of portfolio assessment as a process-oriented assessment mechanism on Iranian EFL students’ English writing ability. Sixty one students of similar writing ability were chosen as the participants of this study. They were divided into two groups. The experimental group received the treatment i.e. portfolio assessment while the control group underwent the traditional assessment. The results of data analysis revealed that the students in the portfolio assessment group outperformed the students in the control group in their overall writing ability and in the sub-skills of focus, elaboration, organization and vocabulary. To triangulate the quantitative data, students' views and reflections about portfolio assessment were elicited via semistructured interviews. The qualitative data underwent thematic analysis and the major extracted themes were discussed. The findings suggest that portfolio assessment empowers students' learning of English writing, hence emphasizing the formative potential of portfolio assessment in EFL classes. The results have some implications for teaching and assessment of L2 writing.